Relationship Perineal Care With Healing Of Perineal Wounds In Postpartum Women On The Sixth Day At Independent Midwife Ermawati Am.Keb Lubuklinggau Practice Year 2024 - Agustina, Novita; Rohani, Tuti; Ayudiah, Febra (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
Background: Based on data from the World Health Organization (WHO) in 2020 there were 2.7 million cases of perineal rupture in maternity mothers. In Asia the incidence of perineal rupture is also a considerable problem in society, 50% of the incidence of perineal rupture in the world occurs in Asia. The number is expected to increase to 6.3 million by 2050 if it does not receive more attention and treatment. (WHO, 2020). Objective of the study: This is to determine the relationship between perineal care and perineal wound healing in sixth day postpartum women at PMB Ermawati Am.Keb Lubuklinggau City. Research Methods: The method used is this research design using analytical observational research design with crossectional research design, data collected by distributing questionnaires to 30 respondents who experienced perineal wounds and in the puerperium during the sixth postpartum day at the Independent Midwife Practice (PMB) Ermawati Am.Keb Lubuklinggau City. Research Results: that of the 30 respondents, almost most of the respondents carried out perineal care well, namely 26 people (86.7%) and those who carried out perineal wound care were less, namely 4 people (13.3%). The results of the bivariate test analysis show that there is a relationship between perineal care and perineal wound healing in postpartum women on the sixth day where the Chi-square test results show that with a p-value of .000 <0.05. Suggestion: Researchers suggest that service institutions can improve the quality of service in handling patients in providing information that proper perineal care can help accelerate the healing process of perineal wounds so that health services are more optimal.